Eat this, not that! 2012 : the no-diet weight loss solution - Zinczenko, David. frey50; Goulding, Matt. (Emmaus, Pa. : Rodale, 2011)
Presents nutritional information for hundreds of popular brand name and restaurant foods, with practical substitutions that can help people cut calories and fat and lose weight.
The year in food -- The truth about your food -- At your favorite restaurants -- At the supermarket -- Holidays & special occasions -- Eat this, not that! for kids -- Cook this, not that!.
Includes index.
Keywords: Nutrition; Functional foods; Convenience foods; Nutrition; Convenience foods -- Health aspects